ҚАРАҚАЛПАҚ ТОЙЛАРЫНДА ѲЗ АРА ЖӘРДЕМ ДӘСТҮРИНИӉ ӘҲМИЙЕТИ - Хожаниязова, Г.М. (ILIM hám JÁMIYET, 2024)
The article examines the issue of the tradition of mutual assistance between relatives, close friends and neighbors at Karakalpak weddings. Modern customs of wedding ceremonies and some traditions related to mutual assistance among the Karakalpaks were also touched upon.